PENGEMBANGAN LITERASI PENDIDIKAN BAGI ANAK- ANAK GAMPONG LANCONG KECAMATAN SUNGAI MAS KABUPATEN ACEH BARAT - Marzuki; Saiful Azmi; Husaidi; Safrida (LP2M Universitas Hasanuddin, 2022)
Lancong village is one of the villages located in Sungai Mas District, West Aceh Regency. the condition of children's educational literacy in Lancong village is not yet in accordance with the mandate of the Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System. Therefore, strategic and appropriate steps are needed to help children improve their literacy. Educational literacy development activities are offered as a solution to the problem of the low literacy level of children in the Lancong village. The objectives of the implementation of this service are: 1) the creation of increased literacy for lancong village children, 2) educating parents and youth in responding to the importance of mentoring learning for children 3) the realization of literacy infrastructure in the form of: libraries and wall magazines. The learning methods applied in the implementation of this service are: Delivering material, sharing sessions, providing infrastructure and learning while playing. Each learning method has its own sub-stages of learning, all of which include: initial socialization, morning motivation, mini library, wall magazine activation, reading every day, writing every day, competitions, rewards, and evaluations. The results of the service show that educational literacy development activities are very useful in supporting educational knowledge for the target audience. — Desa lancong merupakan salah desa yang terletak di Kecamatan Sungai Mas, Kabupaten Aceh Barat. kondisi literasi pendidikan anak di desa Lancong belum sesuai dengan amanat Undang-Undang Republik Indonesia Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional. Oleh karena itu, diperlukan langkah-langkah strategis dan tepat untuk membantu anak meningkatkan literasinya. Kegiatan pengembangan literasi pendidikan ditawarkan sebagai solusi untuk mengatasi permasalahan rendahnya tingkat literasi anak di desa lancong. Tujuan pelaksanaan pengabdian ini adalah: 1) terciptanya peningkatan literasi bagi anak-anak desa lancong, 2) teredukasinya orang tua dan remaja dalam menyikapi pentingnya pendampingan pembelajaran terhadap anak 3) terwujudnya infrastruktur literasi berupa: perpustakaan dan mading. Metode pembelajaran yang diaplikasikan dalam pelaksanaan pengabdian ini adalah Deliver material, sharing session, infrastructure devision serta learn while playing. Pada setiap metode pembelajaran tersebut mempunyai sub tahapan pembelajaran tersendiri yang keseluruhannya meliputi: sosialisasi awal, morning motivation, mini library, aktivasi mading, reading everyday, writing everyday, lomba, reward serta evaluasi. Hasil pelaksanaan pengabdian menunjukkan bahwa kegiatan pengembangan literasi pendidikan sangat bermanfaat dalam penunjangan pengetahuan pendidikan bagi khalayak sasaran.